Mitigating the risk of tube shortages: A blood collection tube validation study conducted in South Africa - Marizna Korf; Jody Rusch; Aye Aye Khine; Nalene Strauss; Lourens Jacobsz; Annalise E. Zemlin; Helena Vreede (African Journal of Laboratory Medicine)
Background: The National Health Laboratory Service was using Becton Dickinson (BD) blood drawing tubes and, in 2021, the supplier notified customers of supply challenges, indicating a risk of global shortages.